From Drama to Transformation as a Person and an Emergency Unit Professional in the Pandemic: A Grounded Theory Approach - Zanferrari, Natália Martins; de Cássia Altino, Rita; Bocchi, Silvia Cristina Mangini [UNESP] (Bentham Science Publishers, 2024)
Background: Pandemic flows have proven increasingly challenging, signaling the need for more effective global policies that benefit healthcare worker safety. Objectives: To understand the health staff's interactional experience in an emergency unit with the COVID-19 pandemic and to develop a theoretical model representative of this experience. Methods: A qualitative research with theoretical saturation through analysis of the 15th non-directive interview, according to Grounded Theory, was developed with physicians, nurses, and nursing technicians in an emergency unit who experienced the pandemic's beginning. Results: The experience unfolded into subprocesses: Considering oneself, at the beginning of the pandemic, as the leading actor of a drama (A); Looking for strategies to cope with the pandemic (B); Transforming as professional and person (C). From dramatic leading role to professional and personal improvement of healthcare staff in emergency services during COVID-19. Conclusion: The model indicated a staff waking up to occupational risks with pathogens in the interface with symbols of the devastating and dramatic concreteness of the SARS-CoV-2 virus and insufficient informational, material, human, and psychosocial resources, encouraging them to use standard precautions even after the pandemic.
Keywords: COVID-19; Emergency medical services; Occupational risks; Pandemic; Patient care team; SARS-CoV-2